A note on the arithmetic of the orthogonal group (1973)
The purpose of this paper is to discuss the maximality as a discrete group of the group GZ of all rational integral matrices of the Real Special Orthogonal Group G = SO (H) for all unimodular integrral symmetric  n   by   n   matrices    H    with signature ( p+r,p), p and gt;1.